Uji Aktivitas Antijamur Ekstrak Etanol Herba Patikan Kebo (Euphorbia hirta L.) Terhadap Candida albicans - Helen Anjelina Simanjuntak; Hermawan Purba; Wan Yuli Anjani; Rahmiati Rahmiati; Toberni S Situmorang (Journal of Natural Sciences, 2022)
The patikan kebo plant is used to cure respiratory infections, malaria, liver, hypertension, gastrointestinal, skin diseases, accelerate wound healing, antidotes, hepatitis, rheumatism and tumors. The purpose of this study was to determine the antifungal activity of patikan kebo. The research method was carried out experimentally with the paper disc diffusion method. The antifungal activity test of each concentration (1%, 2%, 3%, 4%, ketoconazole, DMSO) had respective values (7.14 mm, 7.67 mm, 8.51 mm, 8.80 mm, 26.81 mm, 0 mm). The content of secondary metabolites in the patikan kebo plant are saponins, tannins, alkaloids, steroids/triterpenoids and flavonoids. The patikan kebo plant has medium category antifungal potential.